2016
DOI: 10.1038/ctg.2016.44
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin Exerts Beneficial Effects Independent of its Ability to Alter Microbiota Composition

Abstract: Objectives:Rifaximin has clinical benefits in minimal hepatic encephalopathy (MHE) but the mechanism of action is unclear. The antibiotic-dependent and -independent effects of rifaximin need to be elucidated in the setting of MHE-associated microbiota. To assess the action of rifaximin on intestinal barrier, inflammatory milieu and ammonia generation independent of microbiota using rifaximin.Methods:Four germ-free (GF) mice groups were used (1) GF, (2) GF+rifaximin, (3) Humanized with stools from an MHE patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
82
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 32 publications
9
82
0
1
Order By: Relevance
“…In germfree mice with stool infused from an MHE patient, rifaximin significantly reduced systemic inflammatory cytokines and it was suggested that this effect resulted from a reduction in endotoxin levels and decreased the deconjugation and formation of potentially toxic secondary bile acids. The microbiota composition itself in these mice was not altered by rifaximin [29]. A similar finding is reported in the human setting.…”
Section: Discussionsupporting
confidence: 70%
“…In germfree mice with stool infused from an MHE patient, rifaximin significantly reduced systemic inflammatory cytokines and it was suggested that this effect resulted from a reduction in endotoxin levels and decreased the deconjugation and formation of potentially toxic secondary bile acids. The microbiota composition itself in these mice was not altered by rifaximin [29]. A similar finding is reported in the human setting.…”
Section: Discussionsupporting
confidence: 70%
“…It should be noted that under certain experimental conditions, rifaximin may exert its effects independently of its ability to alter the microbial composition. It was reported that rifaximin therapy ameliorated gut inflammation and endotoxemia in mice treated with humanized microbiota (36). This occurred without alteration in the relative microbial composition.…”
Section: Discussionmentioning
confidence: 98%
“…Before colonization, these were thawed, resuspended in 1.5 mL of sterile PBS per tube/pellet, and then gavaged 0.2 mL per mouse per day. In our prior studies, stool treated in this manner, once thawed and inoculated, could effectively colonize GF mice without complications and with good retention of bacterial profiles …”
Section: Methodsmentioning
confidence: 93%
“…Using established protocols that the NGRRC has developed and published, intact fecal material was transferred to 10‐15‐week‐old GF C57BL/6 mice (both male and female) by daily gavage for 3 days (6‐8 mice/group) . The mice were observed in sterile individually filtered cages for 15 days, after which they were harvested.…”
Section: Methodsmentioning
confidence: 99%